A Case of Transverse Myelitis From Varicella-Zoster Virus in a Patient Who Was Immunocompetent - Deepa Namburi; Caitlin Harmon; Kapil Mehta (Annals of Internal Medicine: Clinical Cases)
Transverse myelitis is a neurologic disorder that stems from focal inflammation of the spinal cord. Varicella-zoster virus can induce this disease, occurring in 0.3% of infected patients. This is a case of a 67-year-old man who presented with headache and weakness. Magnetic resonance imaging scan and cerebrospinal fluid from lumbar puncture confirmed transverse myelitis from varicella-zoster virus. Because of the rarity of the disease, its detection can be missed, and without early recognition and treatment, this condition can cause paralysis and death. This case also underscores the importance of prophylaxis and educating patients on vaccination for prevention of the virus itself.